2019
DOI: 10.1007/978-3-030-36802-9_40
|View full text |Cite
|
Sign up to set email alerts
|

Interpreting Layered Neural Networks via Hierarchical Modular Representation

Abstract: Interpreting the prediction mechanism of complex models is currently one of the most important tasks in the machine learning field, especially with layered neural networks, which have achieved high predictive performance with various practical data sets. To reveal the global structure of a trained neural network in an interpretable way, a series of clustering methods have been proposed, which decompose the units into clusters according to the similarity of their inference roles. The main problems in these stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 24 publications
0
6
0
Order By: Relevance
“…Some previous empirical studies found that neural networks showed modularity and community, so more researchers began empirical research based on community discovery and analysis. Some research work attempts to study the modularity and community structure of neural networks at the neuron level or sub-network level [22][23][24][25][26][27][28][29]. In other research work, the architecture with modular characteristics is trained through parameter isolation or regularization during training, or the degree of modularity is improved, so as to develop a neural network with better modularity [30][31][32][33].…”
Section: Empirical Research Methods For Community Detectionmentioning
confidence: 99%
“…Some previous empirical studies found that neural networks showed modularity and community, so more researchers began empirical research based on community discovery and analysis. Some research work attempts to study the modularity and community structure of neural networks at the neuron level or sub-network level [22][23][24][25][26][27][28][29]. In other research work, the architecture with modular characteristics is trained through parameter isolation or regularization during training, or the degree of modularity is improved, so as to develop a neural network with better modularity [30][31][32][33].…”
Section: Empirical Research Methods For Community Detectionmentioning
confidence: 99%
“…Our work is perhaps most closely related to a series of papers by Watanabe and colleagues (Watanabe et al, 2018;Watanabe, 2019;2020) in which trained networks are decomposed into clusters of "similar" units with the aim of understanding and simplifying those networks. They quantify the similarity of units using a combination of both incoming and outgoing weights.…”
Section: Related Workmentioning
confidence: 97%
“…These methods involve no data or runtime analysis. In contrast, [18], [42], [110], [143], [256] each perform partitioning and cluster analysis based on how neurons associate with inputs and/or outputs. In particular, [110] present a statistical pipeline for quantifying the interpretability of neuron clusters with no human in the loop.…”
Section: Modular Partitionings (Post Hoc)mentioning
confidence: 99%